Pengembangan Potensi Diri Residen Sentra Inyaf Sebagai Cara Bertahan Hidup Tanpa Narkoba Di Masyarakat - Todo Anugrah Simbolon; , Agus Suriadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The differences in resident backgrounds are a challenge for counselors and social workers who working in the rehabilitation of drug abuse. Residents with different backgrounds have different potentials. The potential difference is due to the uneven level of education in society, especially in the lower-middle class. Counselors and social workers must be able to explore and develop the potential of each resident so that after they finish from rehabilitation, they can survive in the community and society will no longer consider them as trash. This can be realized by giving full attention by the counselor to the resident during the rehabilitation process.